"Mérito, desempenho" e "participação": adesões e resistências à meta 19 do PNE nos planos estaduais e distrital de educação - Scalabrin, Ionara Soveral (2018)
The law that established the National Education Plan (PNE) for the 2014-2024 decennium established, in its article 9, the obligation of states, Federal District and municipalities to approve specific laws, disciplining the democratic management of public education in their systems of teaching. PNE's goal 19 is to ensure conditions for the democratic management of education in public schools, which should combine "technical criteria of merit and performance" and "public consultation with the school community", providing resources and technical support from the Union. The way of choosing school management is approached by strategies 19.1 and 19.8, goal 19. The 19.1 strategy stipulates that the selection process should jointly consider "technical criteria of merit and performance" and the participation of the school community ". The 19.8 strategy proposes the application of "specific national exam in order to subsidize the definition of objective criteria for filling positions, the results can be used by adhesion." The general objective of the thesis is to analyze the proposal of association between "merit" and "performance" and "participation" recommended in the PNE for the choice of school directions and the accession / reticence of the states and the Federal District to it, contributing to the debate about the democratic management of the public school, identifying the strategies and explaining the existing mechanisms in the state and district education plans on the process of choosing school management. The research is qualitative, with documentary analysis, which does not dispense the exposition of descriptive content and the use of quantitative data. It focuses on the field of the study of public action, analyzes the policy and its material content (policy), specifies the peculiarities of the institutional framework, the order and structure of political-administrative systems and the legal system in which it is inserted (polity), characterizes the actors, their resources of power and relations and the forms of social mobilization that involve the material content of the public action (politics). The analysis of the education plans of twenty-four states and the Federal District, allows to affirm that fourteen states and the Federal District set out to elaborate specific laws disciplining democratic management, not all the states have done it; in 2017, there were still fifteen states that there was not any democratic management regulation, but six of them did not propose to do so; most states, seventeen, and the Federal District, adhered to goal 19, adjusting to the criteria for receiving resources and technical support from the Union. However, only ten states adhered to strategy 19.1 and only four to strategy 19.8. The analysis of the legislation that establishes the form of choice of the directions of school, effective in July 2018, of the twenty-six states and Federal District, shows that eleven states use technical criteria associated to the consultation of the school community as recommended by PNE, selective process and election; seven states and Federal District adopt the election only; four states employ the selective process and indication; two others make an election and subsequently require approval in the course of training; one makes indication only and one performs public tender.